Survivable biconnected topology for Yemen's optical network - Omar Ba Slaim, Omar Khaled (2021)
Optical fiber has transformed the telecom landscape in the world in the last three decades due to its overwhelming advantages over the other transmission mediums. Optical fibers offer low loss with high bandwidth and long lifespans. There are two challenges for providers of optical fiber technology, namely, the high cost of the optical network infrastructure and equipment and the importance of ensuring network reliability. These issues need to be considered during the deployment of the optical network infrastructure and when we need to expand the existing network. One of the requirements to provide reliability for network traffic is that a network must remain connected in the event of any single node or link failure. The network operators must be able to continue providing reliable important services through their existing network infrastructure and cater to the ever-increasing number of clients. Despite all the benefits of optical communication, many countries are still in the emerging phases in deploying optical communication networks due to the incurred cost. Hence, this study is conducted to assess the best approaches for deploying and expanding an optical fiber network that will lead to better network connectivity, thus help in ensuring the reliability of network services by designing a configuration that meets the desired requirements (e.g., biconnected network) while reducing the overall expenses (e.g., fiber deployment cost). The optimization will be conducted using the CPLEX software.